Fabrication of high aspect ratio nanogrid transparent electrodes via capillary assembly of Ag nanoparticles. Issue 21 (17th May 2016) - Kang, Juhoon; Park, Chang-Goo; Lee, Su-Han; Cho, Changsoon; Choi, Dae-Geun; Lee, Jung-Yong
Abstract : In this report, we describe the fabrication of periodic Ag nanogrid electrodes by capillary assembly of silver nanoparticles (AgNPs) along patterned nanogrid templates. Abstract : In this report, we describe the fabrication of periodic Ag nanogrid electrodes by capillary assembly of silver nanoparticles (AgNPs) along patterned nanogrid templates. By assembling the AgNPs into these high-aspect-ratio nanogrid patterns, we can obtain high-aspect-ratio nanogratings, which can overcome the inherent trade-off between the optical transmittance and the sheet resistance of transparent electrodes. The junction resistance between the AgNPs is effectively reduced by photochemical welding and post-annealing. The fabricated high-aspect-ratio nanogrid structure with a line width of 150 nm and a height of 450 nm has a sheet resistance of 15.2 Ω sq −1 and an optical transmittance of 85.4%.